A influência nos grupos de nativos digitais : uma análise da comunicação na rede Facebook - Vasconcellos, Fernanda Cristine (2015)
Youth changed with the internet and social networks. Young individuals that used to have contact with partners only eventually, can now, through online social networks and mobile devices talk almost all the time with their friends. At the same time, society is changing from a modern environment into a postmodern and complex one, in which human relations and institutions change in importance and dynamics. This dissertation presents a look at these contexts and the characteristics of Young people born on the digital age. It also aims to, through the observation of a group on Facebook, using virtual ethnography and interviews, find elements that allow us to understand how is formed the dynamics of influences on a group of digital born. With these elements, the dissertation designs a panorama of how a Young individual becomes influent on one’s group of friends, which elements give people this role and projects possible consequences of this habit.